Development of a colloidal gold immunochromatographic assay (GICA) for the rapid detection of Spiroplasma eriocheiris in commercially exploited crustaceans from China. Issue 12 (20th June 2017) - Liu, H; Xiu, Y; Xu, Y; Tang, M; Li, S; Gu, W; Meng, Q; Wang, W
Abstract: Spiroplasma eriocheiris is an emerging pathogen in freshwater crustaceans. In recent years, Eriocheir sinensis, Procambarus clarkii, Litopenaeus vannamei, Macrobrachium rosenbergii and Macrobrachium nipponense had been infected by this pathogen in China. An immunochromatographic strip test using gold nanoparticles was developed for rapidly detecting this pathogen. The strip test based on the principle of sandwich immunoassay by the specific combination between the pathogen and polyclonal antibody on a nitrocellulose membrane. Positive samples were displayed as red lines at the test and control zones of the nitrocellulose membrane, while negative samples resulted in a red line only at the control zone. The limit of detection was proved to be 10 6 Color Change Unit/ml. The test strip could be visually detected within 15 min and do not have cross‐reaction with other aquatic bacteria. This test strip allows on‐site rapid detection of S. eriocheiris in crustacean without the requirement of specialized equipment and professional personnel. The one‐step test strips developed in our study had high sensitivity, specificity, reproducibility and stability. In conclusion, this method was proved to be convenient, feasible, rapid and effective for detecting S. eriocheiris .